1998
DOI: 10.1007/s100960050057
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bacteraemia in Patients with Fever and Neutropenia Using 16S rRNA Gene Amplification by Polymerase Chain Reaction

Abstract: Episodes of fever and neutropenia are common complications of treatment for cancer. The use of prophylactic and early empirical antibiotics has reduced mortality but decreases the sensitivity of diagnostic tests based on culture. The aim of this study was to determine the potential of a broad diagnostic approach (eubacterial) based on 16S rRNA gene amplification and sequencing to augment cultural methods of diagnosis of bacteraemia in patients with fever and neutropenia in a regional paediatric oncology centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 0 publications
2
30
0
1
Order By: Relevance
“…Single set of universal primers for PCR followed by sequencing for identification of bacteria has been used by other workers also [10][11][12][13][14]. In this study, we detected bacteria with only one set of PCR primers and used restriction enzyme analysis, instead of species-specific probes or sequencing, to identify bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single set of universal primers for PCR followed by sequencing for identification of bacteria has been used by other workers also [10][11][12][13][14]. In this study, we detected bacteria with only one set of PCR primers and used restriction enzyme analysis, instead of species-specific probes or sequencing, to identify bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown the efficacy of broad range PCR in cases where cultures are rendered sterile by antibiotic administration [10,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 When using rather insensitive bacterial culture techniques, bacteremia could be detected even in subjects with clinically healthy gingiva. The use of more sensitive molecular techniques, such as the polymerase chain reaction, 24,25 would likely prove bacterial translocation from the periodontium to be even more common than presently appreciated. While most studies of dentally related bacteremia have centered around purposeful activities such as tooth brushing, periodontal probing, and tooth extraction, it is possible that while participating in daily activities (chewing, speaking, habits, etc), minor disruptions to gingival integrity occur in a significant number of individuals with gingival inflammation.…”
Section: Gingival Health and Bacteremiamentioning
confidence: 99%
“…PCR technology has been shown to overcome some of the weaknesses of conventional culturing methods in such circumstances [2,4,5]. For instance, in a rat model of Escherichia coli bacteraemia, PCR was shown to yield a detection rate 80% higher than that of blood culture in cefotaxime-treated animals [2].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a rat model of Escherichia coli bacteraemia, PCR was shown to yield a detection rate 80% higher than that of blood culture in cefotaxime-treated animals [2]. Nevertheless, it is still uncertain just how reliable PCR is and whether a negative result truly re¯ects the absence of bacteria in blood [4,5], as mechanisms reducing the availability of the bacterial template DNA may cause false-negative PCR results. When bacteria are killed by antibiotics, DNA may be released and then degraded by human endogenous DNAases.…”
Section: Introductionmentioning
confidence: 99%